Nitrogen species and microbial community coevolution along groundwater flowpath in the southwest of Poyang Lake area, China. (July 2023) - Chen, Xianglong; Wang, Guangcai; Sheng, Yizhi; Liao, Fu; Mao, Hairu; Li, Bo; Zhang, Hongyu; Qiao, Zhiyuan; He, Jiahui; Liu, Yingxue; Lin, Yilun; Yang, Ying
Abstract: Nitrate and ammonia overload in groundwater can lead to eutrophication of surface water in areas where surface water is recharged by groundwater. However, this process remained elusive due to the complicated groundwater N cycling, which is governed by the co-evolution of hydrogeochemical conditions and N-cycling microbial communities. Herein, this process was studied along a generalized groundwater flowpath in Ganjing Delta, Poyang Lake area, China. From groundwater recharge to the discharge area near the lake, oxidation-reduction potential (ORP), NO3 –N, and NO2 –N decreased progressively, while NH3 –N, total organic carbon (TOC), Fe 2+, sulfide, and TOC/NO3 − ratio accumulated in the lakeside samples. The anthropogenic influences such as sewage and agricultural activities drove the nitrate distribution, as observed by Cl − vs. NO3 − /Cl − ratio and isotopic composition of nitrate. The hydrogeochemical evolution was intimately coupled with the changes in microbial communities. Variations in microbial community structures was significantly explained by Fe 2+, NH3 –N, and sulfide, while TOC/NO3 − controlled the distribution of predicted N cycling gene. The absence of NH3 –N in groundwater upstream was accompanied by the enrichment in Acinetobacter capable of nitrification and aerobic denitrification. These two processes were also supported by Ca 2+  + Mg 2+ vs. HCO3 − ratio and isotopic composition of NO3 − . The DNRA process downstream was revealed by both the presence of DNRA-capable microbes such as Arthrobacter and the isotopic composition of NH4 + in environments with high concentrations of NH3 –N, TOC/NO3 −, Fe 2+, and sulfide. This coupled evolution of N cycling and microbial community sheds new light on the N biogeochemical cycle in areas where surface water is recharged by groundwater. Graphical abstract: Image 1 Highlights: NH3 –N, TOC, Fe 2+, and sulfide accumulated in groundwater-surface water exchange zones. Microbial communities along groundwater flowpath are shaped by NO3 –N and Fe 2+ . DNRA-capable microbes were enriched downstream near the lake. Mutual interaction between N cycling and microbial community along flowpath.